How did I experience in digital/online education as a graduate teacher? - Réti, Júlia (Autonomy and Responsibility Journal of Educational Sciences, 2022)
As a Hungarian Literature and Grammar and English as a Foreign Language teacher with a 5-year work experience, I started online education in a secondary school in Budapest to which students of very different age groups attend to. Thus, I had the opportunity to experience a huge variety of challenges of the new digital educational system first-hand, since I was teaching both of my subjects in the 5th, 7th, 8th, 10th and 11th grades. Teaching a wide range of age groups demands the knowledge and use of diverse approaches even in the traditional educational form, not to mention the adversities of the students’ different presence and activity in the digital space. I intend to present my experiences, observations, successful activities and ideas which I have collected since March of 2020 trying to provide practical help to those who are new to this profession as well as those who have experienced online teaching and its difficulties themselves. The motivation of writing this paper is to collect inspiring ideas for teaching online since several colleagues of mine had had the experience of isolation and helplessness during these highly unusual circumstances which were and are still present in the pandemic.